Minding the gap: Asymmetric effects of pay dispersion on stakeholder engagement in corporate environmental (Ir)responsibility - ZHANG, Ying (Institutional Knowledge at Singapore Management University, 2020)
How does pay dispersion affect corporate environmental performance? Building on the tournament effect and equity perspective, we theorize that vertical pay dispersion and horizontal pay dispersion can impinge on corporate environmental performance. We develop the theoretical argument that vertical pay dispersion is negatively related to corporate environmental responsibility (CER) and positively related to corporate environmental irresponsibility (CEIR) due to the tournament competition among executives, and that horizontal pay dispersion is negatively related to CER and positively related to CEIR due to the unjust sense among executives. We then delve into the asymmetric effects of vertical pay dispersion and horizontal pay dispersion on CER and CEIR. We argue that the asymmetric effects result from the difference in social comparison. We find strong empirical support for our predictions. Implications for the development of the literature on pay dispersion and corporate environmental performance are discussed.